Irrigation groundwater quality based on hydrochemical analysis of Nandgaon block, Nashik district in Maharashtra - Aher, Kailash; Gaikwad, Sharad (International Journal of Advanced Geosciences, 2017)
To identify the sources and quality of groundwater, the water samples were collected from 52 dug wells irrigation water in an area of 1089.82km2 and were analyses for pH, Conductivity, total dissolved solids, Calcium, Magnesium, Sodium, potassium, total hardness, Alkalinity (CO32−, HCO3−), sulphate, chloride, nitrate and fluoride to understand the (irrigation water quality index ) IWQI, The         secondary parameters of irrigation groundwater quality indices such as Sodium adsorption ratio (SAR), Residual sodium carbonate (RSC), Kelley’s ratio (KR), Sodium soluble percent (SSP), Permeability index (PI),Magnesium adsorption ratio (MAR),and CRI       (Corrosively ratio index) were calculated from the primary parameter for irrigation water quality index (IWQI). The IWQI was classified into excellent to unfit condition of groundwater quality based on their Water Quality Index (WQI). The IWQI (88%+12%) indicate that slightly unsustainable to good quality of ground water. But due to this quality deterioration of shallow aquifer, an immediate attestation requires for sustainable development.